MOTIVASI HEDONIC SHOPPING PADA GENERASI Z DI KOTA BANDUNG - Ria Arifianti; Farah Putri Firsanty (JURNAL LENTERA BISNIS, 2025)
The phenomenon of shopping is an interesting discussion from a social and economic perspective, the development of the era has given rise to various choices of shopping methods with the aim of making it easier for buyers to access the goods and services they will buy, one of which is online shopping which is increasingly popular among young people, especially generation Z. This study aims to explain how hedonic shopping motivation is carried out by Gen Z, how they choose to shop not only to meet their needs but also the choice is based on providing emotional pleasure and satisfaction and following certain trends that are currently popular in society or commonly known as Fear of Missing Out (FOMO). This study uses the theory of hedonic shopping motivation according to Hirschman and Holbrook (1982) who developed the concept of hedonic shopping types which state that a consumer gets satisfaction from the shopping experience regardless of the benefits or uses obtained from purchasing the goods as an analytical tool for evaluating hedonic shopping motivation in generation Z in Bandung City. This descriptive research conducted aims to create a systematic, factual, and accurate description or picture of the implementation of hedonic shopping motivation in the retail industry. Based on the analysis results, it was found that hedonic shopping motivations were driven by adventure shopping, gratification shopping, role shopping, value shopping, social shopping, and idea shopping.